Marketing Strategy: A Decision Focused Approach - Walker Orville C (Mc Graw-Hill, 2010)
Marketing Strategy, 7e is a focused, succinct text which can be used on its own or packaged with a case book. It covers the concepts and theories of creating and implementing a marketing strategy and offers a focus on the strategic planning process and marketing’s cross/inter-functional relationships. This text distinguishes itself from competitors by maintaining a strong approach to strategic decision making. The Seventh Edition helps students integrate what they have learned about analytical tools and the 4P’s of marketing within a broader framework of competitive strategy. Four key and relevant trends that are sweeping the world of marketing theory and practice are integrated throughout this new edition.